1990
DOI: 10.1093/rheumatology/29.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Hip Joint Ultrasonography: Correlation With Intra-Articular Effusion and Synovitis

Abstract: The ultrasonographic distance between the collum of the femur and the capsule of the hip joint was measured in 88 hips of 75 patients with chronic inflammatory joint disease and with hip joint symptoms or signs. In addition, 10 other hips were measured before soft tissue operation of the hip joint. The ultrasonographic distance was 7 mm or more in 29 out of 33 hips with synovial fluid in joint puncture and in seven out of nine hips with intra-articular effusion or synovitis in open surgery. Intra-articular inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Joint effusion or synovitis distends the capsule outwards and the anechogenic distance between bone and capsule lengthens. 17 The following criteria were used to assess the eligibility of study participants: patients with complete ankylosis of the spine; patients with unilateral or bilateral synovial hyperplasia, and/or effusions of the hip assessed by ultrasonography; patients without previous history of tuberculosis, hepatitis, and other infection diseases; patients in agreement with etanercept treatment. In patients with bilateral synovitis of the hip, we mainly focused on the more severely affected side.…”
Section: Introductionmentioning
confidence: 99%
“…Joint effusion or synovitis distends the capsule outwards and the anechogenic distance between bone and capsule lengthens. 17 The following criteria were used to assess the eligibility of study participants: patients with complete ankylosis of the spine; patients with unilateral or bilateral synovial hyperplasia, and/or effusions of the hip assessed by ultrasonography; patients without previous history of tuberculosis, hepatitis, and other infection diseases; patients in agreement with etanercept treatment. In patients with bilateral synovitis of the hip, we mainly focused on the more severely affected side.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several studies have demonstrated that high frequency US is accurate for detecting joint effusion [7][8][9][10][11][12][13][14][15][16] and synovitis, 7-11 15 17-19 , compared with magnetic resonance imaging (MRI) 10 12 14 17 and direct arthroscopic visualisation. [20][21][22] US is more sensitive and reproducible than clinical evaluation in assessing joint inflammation.…”
mentioning
confidence: 99%
“…A difference of effusion thickness greater than 2 mm in children and 1 mm in adults should raise concern for a pathologic effusion. [17][18][19][20] Although often dark and anechoic, effusions can be heterogeneous, especially in cases of purulent effusion. 21 Unfortunately, ultrasound characteristics of a hip effusion lack the accuracy to distinguish a septic from an aseptic effusion.…”
Section: Identifying a Hip Effusionmentioning
confidence: 99%